Estimated Levator Ani Subtended Volume: A Predictive Biomarker for Surgical Outcomes Following Native Tissue Apical Repair. Issue 6 (4th June 2022) - Wyman, Allison M.; Salemi, Jason L.; Lai-Yuen, Susana; Greene, Kristie A.; Bassaly, Renee; Kedar, Rajendra; Hoyte, Lennox
Abstract : Objective: The aim of the study was to investigate the clinical utility of estimated levator ani subtended volume (eLASV) as a prospective preoperative biomarker for prediction of surgical outcomes. Study Design: This is a prospective case-control pilot study. Patients were recruited and gave consent between January 2018 and December 2020. Surgical failure was defined by composite score. The eLASV was calculated for each patient based on a previously published algorithm. Descriptive statistics, Fisher exact test, log-binomial regression, area under a receiver operating characteristics, Bland-Altman plot, Lin coefficient, and κ coefficient were all performed for analysis. Results: Fifty-one patients gave consent, 31 completed preoperative magnetic resonance imaging, 27 underwent surgery (uterosacral ligament suspension), and 19 followed up for 1-year examination. Five patients (26.3%) were defined as surgical failure with median eLASV volume of 57.0 (interquartile range, 50.1–66.2). Fourteen patients (73.7%) were defined as surgical success with median eLASV of 28.2 (interquartile range, 17.2–24.3). Eighty percent of the surgical failure group (4/5) had elevated volume of eLASV, where only 14.3% of the success group (2/14) had an elevated volume ( P = 0.0173). No confounders were found and unadjusted log-binomial regression suggested that patients with a high eLASV were 8.7 (95% confidence interval, 1.2–61.9) times more likely to experience surgical failure compared with those with low eLASV. The c-statistic (area under a receiver operating characteristics) was high at 0.829 along with Lin concordance coefficient of 0.949 (95% confidence interval, 0.891–0.977) for continuous data between the 2 interrater observer teams. Conclusions: In this small prospective pilot study, patients with elevated eLASV on a preoperative pelvic magnetic resonance imaging were associated with an increased risk for surgical failure at 1 year regardless of age, body mass index, stage, or parity. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03534830